2020
DOI: 10.1186/s12939-020-01168-6
|View full text |Cite
|
Sign up to set email alerts
|

Need and inequality in the use of health care services in a fragmented and decentralized health system: evidence for Argentina

Abstract: Background: The high fragmentation and decentralization in the provision of health care services that characterizes Argentina's health system, as well as the economic and social inequalities, challenge the achievement of the Universal Health Coverage (UHC). The objective of this study is to measure socioeconomic-related inequality and horizontal inequity in the use of health care services in Argentina as well as identify the factors that contribute to these disparities. Methods: The 2013 National Risk Factor S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…In Argentina, a greater percentage of the population in the interior provinces has a lower socioeconomic status and lacks health-care insurance 18 , 19 . Additionally, interior-region medical centers have fewer specialists 17 ; these documented disparities include orthopaedic surgeons. The difficulty in procuring implants not only results in delayed care but also affects the type of surgery performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Argentina, a greater percentage of the population in the interior provinces has a lower socioeconomic status and lacks health-care insurance 18 , 19 . Additionally, interior-region medical centers have fewer specialists 17 ; these documented disparities include orthopaedic surgeons. The difficulty in procuring implants not only results in delayed care but also affects the type of surgery performed.…”
Section: Discussionmentioning
confidence: 99%
“…Exterior hospitals, as defined in this study, generally have more resources than interior hospitals [17][18][19] . Underscoring this discrepancy in resources, a recent study measured Argentinians' use of health-care services and determined that there is greater use of services by those with higher levels of per capita income 17 . Furthermore, more than one-third (36%) of patients in the interior group have no insurance and rely on government-related health-care insurance and personal resources 20 , which can delay the ability to acquire necessary implants for surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the Obras Sociales fare better than others, and these are superior, in general, to the public services. On the other hand, there are important regional differences: between the capital and the suburbs of Buenos Aires (the conurbado), as well as between the capital and the provinces (Palacios et al, 2020). Financial and infrastructure resources are highly concentrated in Buenos Aires, Cordoba, and Rosario.…”
Section: The Health Regimes In the Face Of The Pandemicmentioning
confidence: 99%
“…Within these packages of reforms were those aimed at decentralizing and restructuring public healthcare provision during the 1990s [ 1 ]. As a result of these and other policies, Palacios, Espinola and Rojas Roque [ 2 ] found that the Argentine health system shows pro-rich inequality in the use of public services, and that this is fueled by the inequitable distribution of access to the social security institute and to the private healthcare sub-system. Bernales-Baksai [ 3 ] addresses the issue in Chile and Uruguay, countries with seemingly strong health system in the region, and shows how their policy architectures tackle segmentation.…”
mentioning
confidence: 99%